HEALING POTENTIAL OF A POLYHERBAL OINTMENT ON EXCISION WOUND IN NORMAL AND DIABETES INDUCED ALBINO RATS - M, Kadhiravan; K, Keerthana; G, Shobana; G, JOTHI; J, Radhika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Wound healing potential of polyherbal ointment prepared from Cordial oblique Willd., Dentophote falcate (L.f) Ettingsh., and Vigna radiate Linn. has been evaluated, Preclinical studies were carried out using albino rats as experiment models. Methods: Animals were divided into 6 groups, each groups comprising of 6 rats. Group I, II and III are normal excision wounded rats that were categorized as normal untreated, polyherbal ointment treated and standard ointment treated respectively. Groups IV, V and VI were induced with diabetes using alloxan monohydrate (150mg/kg bw; ip single dose) and grouped into diabetic untreated, polyherbal ointment treated and standard ointment treated respectively. The polyherbal ointment was prepared by using aqueous extracts of plants in equal proportion with simple ointment base (15% w/w). The Physical, Biochemical and enzymatic parameters studied were rate of wound contraction, ascorbic acid, hydroxyproline, hexosamine, SOD, LPO, serum protein, granulation tissue protein, serum glucose, DNA, RNA, platelet and WBC. Results: The excision wounded animals treated with polyherbal ointment showed a higher rate of contraction and epithelialization during the treatment period. Group II showed 100% and group V showed 90% wound contraction at the end of experimental period. Hydroxyproline, hexosamine, ascorbic acid, tissue protein, DNA, RNA levels and SOD activity were increased significantly (p<0.05), LPO, platelet and serum protein level were decreased with polyherbal ointment treated groups compared to control and standard groups. Conclution: The present study substantiates the traditional claims of plants prepared as polyherbal ointment possessing significant wound healing promoting activity and provides scientific evidence to the ethno medicinal property of plants in healing wounds. Keywords: Wound healing, Polyherbal ointment, Hydroxyproline, Hexosamine, Excision wound, Cordia obliqua Willd., Dentophote falcate (L.f) Ettingsh., Vigna radiata Linn.